Enhancing biological nitrogen and phosphorus removal performance in aerobic granular sludge sequencing batch reactors by activated carbon particles. (1st February 2022) - Sarvajith, M.; Nancharaiah, Y.V.
Abstract: Long start-up periods for aerobic granular sludge (AGS) formation and establishment of P removal pathways are challenges for widespread implementation of AGS process. External additives such as activated carbon (AC) attracted interest for accelerating AGS formation. However, the roles of AC in granulation and biological nutrient removal (BNR) are not understood. Here, the role of AC was investigated in decreasing start-up periods in AGS formation and BNR under different carbon substrate conditions (i.e., acetate (HAc), propionate (HPr) and HAc-HPr) in sequencing batch reactors (SBRs). AC addition increased aggregation index and settleability of activated sludge (AS) inoculum which minimized AS washout from SBRs. AC addition hastened AGS formation and establishment of BNR pathways by facilitating AS retention and biofilm formation. Feeding HAc or HAc-HPr supported better granulation (MLSS: 6–7 g l −1, SVI: 30–40 ml g −1 ) than HPr (MLSS: 4 g l −1, SVI: 70). The start-up periods for efficient total nitrogen (TN) removals were decreased to 22 and 16 d from 38 to 25 d, respectively, in AC augmented SBRs fed with either HAc or HAc-HPr. TN removals were higher at ≥95% in HAc or HAc-HPr fed SBRs. Total phosphorus (TP) removals were also higher in AC-augmented SBRs at 80% and ≥90% in HAc and HAc-HPr fed SBRs, respectively. In contrast, TN and TP removals were lower at 70% and 35%, respectively, in HPr fed SBR. Ammonium was primarily removed via nitritation-denitritation pathway. Phosphorus removal was at 1.7 to 2-fold higher in AC augmented SBRs and driven by enhanced biological phosphorus removal (EBPR) pathway. MiSeq sequencing and qPCR revealed higher enrichment of polyphosphate accumulating organisms (PAOs), denitrifying PAOs, and ammonia oxidizers in AC-augmented SBRs fed with HAc or HAc-HPr. This study demonstrates that AC addition can be considered for enrichment of PAOs and establishment of EBPR in aerobic granular SBRs. Graphical abstract: Image 1 Highlights: Settleability of activated sludge (AS) was increased by activated carbon (AC) particles. Washout of AS inoculum was effectively minimized during start-up in granular SBRs. Nitrogen and phosphorus removals were in SBRs using acetate or acetate-propionate. AC particles decreased start-up periods for achieving efficient total nitrogen removal. P removal was 2-fold higher via EBPR pathway in SBRs augmented with AC particles.